The relationship between cellulose nanocrystal dispersion and strength. (30th August 2016) - Cao, Yizheng; Zavattieri, Pablo; Youngblood, Jeffrey; Moon, Robert; Weiss, Jason
Highlights: Studied agglomeration of cellulose nanocrystals (CNCs). Used tip ultrasonication to disperse the CNCs and improve strength of up to 50%. The critical CNC concentration in pore solution 0.18 vol%. Abstract: This paper studies the agglomeration of cellulose nanocrystals (CNCs) and uses ultrasonication to disperse CNCs in cement pastes in an attempt to improve strength. Rheological measurements show that when the concentration of CNCs exceeds 1.35% by volume in deionized water, agglomerates start to develop. This experimental finding is comparable to the value obtained from a geometrical percolation model (1.38% by volume). When the matrix phase (deionized water) is replaced with a simulated cement paste pore solution, the CNCs begin to agglomerate at a lower concentration (approximately 0.18% by volume). The CNC concentration of 0.18% corresponds to the concentration of CNCs in cement paste where the maximum strength is reached. Tip ultrasonication was found to effectively disperse the CNCs and the cement pastes obtained strength improvements of up to 50%, which is significantly better than the strength improvement of raw CNCs alone (20–30%).